2019
DOI: 10.1093/hmg/ddz239
|View full text |Cite
|
Sign up to set email alerts
|

The variability of SMCHD1 gene in FSHD patients: evidence of new mutations

Abstract: In this study, we investigated the sequence of (Structural Maintenance of Chromosomes flexible Hinge Domain containing 1) SMCHD1 gene in a cohort of clinically defined FSHD (facioscapulohumeral muscular dystrophy) patients in order to assess the distribution of SMCHD1 variants, considering the D4Z4 fragment size in terms of repeated units (RUs; short fragment: 1–7 RU, borderline: 8-10RU and normal fragment: >11RU). The analysis of SMCHD1 revealed the presence of 82 variants scattered throughout the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
5
14
0
Order By: Relevance
“…We did not analyze the short sequence-length polymorphism in all participants, given that several studies have shown that different haplotypes can be carried by patients with FSHD. [5][6][7][8][9][10][11][12] The carriers of DRA with 7 to 8 RUs represent 20% of all carriers accrued by INRF (eFigure 1 in the Supplement). We enrolled only patients for whom clinical evaluation was performed with the CCEF by a properly trained physician who belonged to the Italian Clinical Network for FSHD (ICNF).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not analyze the short sequence-length polymorphism in all participants, given that several studies have shown that different haplotypes can be carried by patients with FSHD. [5][6][7][8][9][10][11][12] The carriers of DRA with 7 to 8 RUs represent 20% of all carriers accrued by INRF (eFigure 1 in the Supplement). We enrolled only patients for whom clinical evaluation was performed with the CCEF by a properly trained physician who belonged to the Italian Clinical Network for FSHD (ICNF).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…It has to be noted that SMCHD1 variants as well as D4Z4 hypomethylation in the presence of the haplotype 4qA/PAS distal to the D4Z4 array have been found in patients with bosma arhinia and microphtalmia syndrome, a congenital disease with no associated muscle phenotype. [5][6][7][8][9][10][11][12] The classic FSHD phenotype is characterized by onset in the first or second decade of life with progressive facial, shoulder girdle, and pectoral muscle weakness and atrophy, often asymmetric. 13 Disease progression may lead to the involvement of abdominal muscles and distal lower extremity weakness, causing a steppage gait before impairment of pelvic girdle muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Patients of both classes harbor a DUX4 allele with a polyadenylation signal. However, 95% of patients (FSHD1) have a deletion of between one and 10 large repeated units of D4Z4 and the rest (FSHD2) inherit a mutation in the SMCHD1 or DNMT3B genes [148][149][150]. SMCHD1 and DNMT3B also act as modifiers of disease severity in FSHD1 subjects [149,151].…”
Section: Facioscapulohumeral Muscular Dystrophymentioning
confidence: 99%
“…The main features of DNA methylation abnormalities in human monogenic diseases are listed in Table 1. [145][146][147][148][149][150][151][152][153][154] Loss of methylation (LOM); gain of methylation (GOM); uniparental disomy (UPD); full mutation (FM); premutation (PM); methylation-specific (MS); multiplex ligation probe-dependent amplification (MLPA); paternal (Pat); maternal (Mat); Beckwith-Wiedemann syndrome (BWS); Silver-Russell syndrome (SRS); Transient Neonatal Diabetes Mellitus (TNDM); pseudohypoparathyroidism 1b (PHP1b); Multi-Locus Imprinting Disturbances (MLID); Facioscapulohumeral Muscular Dystrophy (FSHD).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this patient satisfied the diagnostic criteria of SOD 23 . Physical evaluation detected no clinical features indicative of FSHD2 26,27 , except for mild fatigability, mild mental retardation, and slight instability in walking on tiptoes and heels (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%